DISKURSUS SENGKETA LAUT TIONGKOK SELATAN DI MEDIA SOSIAL TWITTER - Dienda Audra Syari; Muhammad Isnaini (Universitas Lambung Mangkurat, 2022)
This study aims to examine some of the literature on the impact of the South China Sea dispute from the perspective of global communication from the perspective of social media Twitter. The method used is a qualitative approach. This study is to find out how many sources on social media Twitter discuss this global issue and its impact on other countries. The results showed: 1) Since 2012 until now, several sources have discussed the development of studies on the South China Sea Ownership Dispute in the perspective of global communication. Of the many accounts registered on social media Twitter that discuss the issue of the South China Sea, there are 28,031 active authors and 2,412 identified authors who have searched for articles published between the last 5 to 15 years. The results found 21 studies / studies published from Asia, America, and Australia related to the discussion of the South China Sea Ownership Dispute issue from a global communication perspective. The South China Sea dispute is one of the threats that has the potential to have a large negative impact, not only for Indonesia, but also for regional stability in Southeast Asia. 2) The impact arising from the South China Sea Ownership Dispute that I got from qualitative analysis from social media sources Twitter, namely through ASEAN, it is likely that this conflict can be resolved peacefully. In addition, this conflict is able to create global cooperation in several fields between countries regarding the management of the South China Sea area, so that it is expected to be able to calm disputes with the existence of collaborations that build towards a better direction.